Development of P3D Learning Strategy Using Google Sites to Support 21st-Century Skills - Mukhoyyaroh, Qiswatun; Miharja, Jajang; Baldah, Beti; Yuniarti, Anisyah (Biosfer: Jurnal Tadris Biologi, 2022)
This research aims to create a product (a P3D learning strategy using google sites to support 21st-century skills). This research employed Hannafin and Peck's Research and Development (R & D) method. A needs assessment (need assessment), product design (product design), product development, and implementation comprise the research design (development and implementation). Teacher and student interview sheets, media, material expert validation questionnaire sheets, and teacher and student answer sheets are among the instruments employed. Techniques for gathering data include interviews and questionnaires. Data analysis for interviews was accomplished by data reduction, data presentation, and conclusion drawing, whereas data analysis for questionnaires was accomplished through quantitative and qualitative methods. The study's population consisted of senior high school science-majored students in Lebak Regency, with a sample size of 30 from SMAN 1 Bojongmanik and 30 from SMAN 3 Cibeber. The product feasibility test, conducted by two media experts and two material experts, revealed that this product was feasible with an average value of 77%.ABSTRAK: Tujuan Penelitian ini untuk menghasilkan produk (strategi pembelajaran P3D menggunakan google sites untuk menunjang keterampilan abad 21). Metode penelitian menggunakan Research-Development (R & D) dengan desain penelitian yang dikembangkan oleh Hannafin and Peck. Desain penelitian terdiri dari penilaian kebutuhan (need assessment), desain produk (product design), pengembangan dan implementasi produk (development and implementation). Instrumen yang digunakan antara lain lembar wawancara guru dan siswa, lembar angket validasi ahli media dan materi, lembar respon guru dan siswa. Teknik pengumpulan data menggunakan wawancara dan angket. Analisis data untuk wawancara dilakukan dengan cara mereduksi data, penyajian data dan penarikan kesimpulan sedangkan analisis data pada angket dengan cara kuantitatif dan kualitatif. Populasi penelitian merupakan siswa dan siswi SMA MIPA di Kabupaten Lebak dengan sampel berjumlah 30 orang dari SMAN 1 Bojongmanik dan 30 orang dari SMAN 3 Cibeber. Hasil uji kelayakan produk oleh dua ahli media dan dua ahli materi menunjukan bahwa produk ini layak untuk digunakan dengan nilai rerata sebesar 77%.